Steady-state response of rectangular plate with four free edges supported at internal points. (August 2020) - Cao, Liang; Chen, Y. Frank; Liu, Jiepeng
Abstract: The steady-state response of a rectangular plate with four free edges supported at internal points subjected to external force is determined. The general analytical solution is obtained by a hybrid method that decomposes the original structure into four basic rectangular plates with different boundary conditions. A numerical example is presented to show that the high-degree accuracy can be gained with a small effort of calculations using the theoretical solution. Sensitivity studies using the analytical solution were also conducted to investigate the effects of load magnitude, sectional dimension (or area), bending stiffness of rectangular plate, and location of internal point on the support reaction, displacement, bending moment, and shear force of rectangular plate.